Disability pension and sociodemographic & work-related risk factors among 2.3 million migrants and natives in Finland (2011–2019): a prospective population study - Haider Waseem; Salonen Laura (Springer Nature, 2025)
Background
Increasing employment and immigration have been proposed as possible solutions to tackle the problem of the labour force shortage in aging societies. Ensuring sufficient health and work ability among migrants is a key factor in increasing and maintaining their employment. Many studies have found higher disability pension (DP) rates among migrants compared to natives but such studies lack in determining the risk of DP by occupational class and industrial sector. This study explores the risk of DP and the contribution of sociodemographic and work-related factors between migrants and natives in Finland.
Methods
Full-population panel data obtained from the administrative registers of Statistics Finland were used to study 2.3 million individuals aged 25–60 years in 2010. We calculated hazard ratios (HR) and their 95% confidence intervals (CI) to estimate the risk of having a DP in 2011–2019 using Cox proportional hazard models adjusting for different sociodemographic and work-related factors.
Results
Compared to natives, migrants had a lower risk of a DP (HR 0.58, 95% CI 0.53–0.63). We found great variation between countries of origin, where compared to natives, migrants from refugee-exporting countries (HR 1.37, 95% CI 1.22–1.53) and other non-European countries (HR 1.30; CI 1.18–1.43) had a higher risk of DP, but migrants from other countries did not differ or had a slightly lower risk of DP than natives. The associations between sociodemographic factors and the risk of DP were very similar between natives and migrants.
Conclusion
Migrants had a lower risk of a DP than natives except for migrants from outside Europe. The associations between different sociodemographic and work-related factors and the risk of DP were similar between natives and migrants and did not completely explain the differences in the risk of DP.